Penerapan Sistem Informasi Manajemen Rumah Sakit (SIMRS) dan Pemahaman Sumber Daya Manusia (SDM) Terhadap Kualitas Laporan Keuangan Rumah Sakit: Studi Kasus Pada RSKIA SADEWA - Adhitya Tri Wibowo; Muhamad Rifandi (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
Hospitals are required to carry out their operational activities in a professional manner, starting from systematic data management, preparing financial reports according to standards, making and implementing policies so that they must be able to carry out their operational activities effectively and efficiently. The application of the hospital management information system is expected to help management, especially in making decisions that are fast, precise and accurate based on the information generated by the system. This study aims to determine the effect ofthe application of hospital management information systems and understanding of human resources (HR) on the quality of hospital financial reports (a case study at RSKIA Sadewa). This research is a quantitative study using a descriptive approach. The data used in this study were primary data and secondary data. Data collection methods in this study used questionnaires, observation and documentation. The sampling technique used non-probability sampling technique. The validity test used the Pearson Product Moment correlation test, while the reliability test used Cronbach Alpha. The data analysis technique used multiple regression analysis techniques using the SPSS 22 program. Based on the results of this study it can be concluded that the Implementation of Hospital Management Information Systems and Understanding of Human Resources (HR) both simultaneously and partially have a positive and significant effect on quality of hospital financial reports. This research is expected to be used as a reference for future researchers with the same research object.